Is useful<span> in </span>proving<span>various theorems about </span>triangles<span> and other polygons.
</span>
The answer to your question would be w=9
1 ║ 1 2 -3 2
1 3 0
--------------------------------------------------------------------
1 3 0
⇒ The Remainder is 2
Answer:
D. X=-3, y=4
Step-by-step explanation:
-2x+3y=18 equation 1
x=-y+1 equation 2
-2(-y+1)+3y=18 replace x value of equation 2 into equation 1
2y-2+3y=18
5y=20
y=4
solve for x by replacing y value into either equation.
x=-y+1
x=-4+1
x=-3